DESIGN AND BUILD POS WEBSITE SOFTWARE FOR CV DIGITAL PRINTING BASED ON VISUAL CODE SOFTWARE USING THE IGNITER CODE FRAMEWORK 3 - Popon Handayani; Ade Setiawan; Santoso Setiawan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study designs a web-based Point of Sale (POS) system for CV Digital Printing, focusing on requirements analysis, user-level page allocation, database design, software architecture, and associated costs. The primary goal is to streamline and expedite sales transactions, product stock management, sales reporting, and customer data management. The main page is divided into